The Systematics, Morphological, and Molecular Characterization of Economically Important Plant–Parasitic Nematodes: A Themed Issue in Honor of Dr. Gary Bauchan - Handoo, Zafar; Kantor, Mihail (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nematodes are one of the most important pests globally and can cause up to 14% loss of food crops. In total, nematodes cause over USD 100 billion in global crop damage annually. To date, only a few thousand PPN species have been described. Nematode identification has traditionally relied on morphological and anatomical characters using light microscopy and, in some cases, scanning electron microscopy (SCN). Lately, integrative studies combining molecular diagnosis with morphology and taxonomy have been used to accurately identify and describe nematode species. Detailed analyses of morphological and molecular data have both significantly contributed to our overall understanding of the dynamic and complex nature of plant-nematode interactions. This book includes eleven chapters that cover different aspects of nematology research, from classical morphology and taxonomy to DNA analysis and phylogeny. It also includes very useful information on the rapid detection of plant-parasitic nematodes.